Social inclusion and social capital of the Shanghai Library as a community place for self-improvement. Issue 2 (12th June 2019) - Lo, Patrick; He, Minying; Liu, Yan
Abstract : Purpose: Using a Shanghainese context, the purpose of this paper is to understand the effects of the public library in its community, as well as its ability to create social capital. Along with this, this paper aims to look at some socially disadvantaged groups within Shanghai and see the positive benefits that the Shanghai Library (SHL) has in society. Design/methodology/approach: Using a total of 410 respondents from Shanghai through a questionnaire, this study investigates how different groups of disadvantaged groups (namely, students, elderly and unemployed) living in Shanghai perceived the social values, and contributions functions of the SHL to the local community, and its capacities to create social capital. Findings: Findings of this study indicate that respondents expressed an overall highly positive outlook of the SHL's value to the community, and they found it to have an important role in their daily lives. Originality/value: This study will be useful for understanding the roles of the public library in a Chinese context, as well as the views and perceptions of the public library to disadvantaged user groups in China.